March 2014 Phoenix pulmonary journal club: palliative care - Mathew M (Southwest Journal of Pulmonary and Critical Care, 2014)
No abstract available. Article truncated at 150 words. Temel JS, Greer JA, Muzikansky A, Gallagher ER, Admane S, Jackson VA, Dahlin CM, Blinderman CD, Jacobsen J, Pirl WF, Billings JA, Lynch TJ. Early palliative care for patients with metastatic non-small-cell lung cancer. N Engl J Med. 2010 Aug 19;363(8):733-42. The March journal club focused on the role of palliative care in respiratory diseases such as chronic obstructive lung disease (COPD) and lung cancer. Palliative care is specialized care that focuses on life threatening disease and the relief of pain and stress. Although often initiated near the end of life, palliative care should not be considered as end of life care. This study reviewed the impact of introducing palliative care in conjunction with oncologic care in the treatment of metastatic non-small cell lung cancer versus oncologic care alone. This was a nonblinded, randomized control trial of 151 patients done at the Massachusetts General Hospital. Seventy-seven patients were randomly assigned ...